2022
DOI: 10.3390/ani12202857
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electroencephalography in Preslaughter Management: A Review

Abstract: Electroencephalography (EEG) can be reliable for assessing the brain’s electrical activity of preslaughter stress and pain. The duration between the ventral neck cut and induction of a state of unconsciousness/insensibility is crucial in the slaughtering of animals, reducing pain, fear, and distress. Various EEG variables, such as median frequency (F50), the total power of EEG spectrum (Ptot), waves patterns (amplitude and frequencies), epileptiform EEG, index of consciousness, and isoelectric EEG, are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 137 publications
0
11
0
Order By: Relevance
“…The total power of the EEG spectrum (Ptot) (Cohen’s d value- −0.34) showed a non-significant increase during the treatment phase as compared with the control phase ( Figure 4 ). The Ptot of the EEG spectrum correlates with the relaxed phase of animals, with animals in the relaxed phase usually having lower power [ 27 ]. The median frequency (MF or F50) of the EEG spectrum was recorded as significantly ( p = 0.002) higher in the treatment phase compared with the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total power of the EEG spectrum (Ptot) (Cohen’s d value- −0.34) showed a non-significant increase during the treatment phase as compared with the control phase ( Figure 4 ). The Ptot of the EEG spectrum correlates with the relaxed phase of animals, with animals in the relaxed phase usually having lower power [ 27 ]. The median frequency (MF or F50) of the EEG spectrum was recorded as significantly ( p = 0.002) higher in the treatment phase compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, electroencephalogram (EEG) has increasingly been used for assessing pain and stress during the slaughter of livestock [ 27 ]. It is a technology used to measure the electric activity of neurons in the cerebrocortical region of the brain by fixing electrodes on various positions of the brain [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary science, the response to stressors was studied with a neurocognitive lens. Pavan Kumar et al [2022] found out how EEG is the accurate predictor of unconsciousness in response to noxious and painful stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Pain refers to a "discriminative sensation comprising emotional experience caused by actual or potential tissue damage" [6]. The perception of pain is protective and warns animals against situations that may damage tissues and avoid these situations in the future [7]. A noxious stimulus is a stimulus that causes or may cause tissue damage, thereby causing pain perception.…”
Section: Introductionmentioning
confidence: 99%
“…There is a perception among some scholars and researchers that stunning causes more pain to animals than slaughtering [19,45,46]. However, this could be primarily due to the chances of mis-stun and associated hyperalgesia leading to compromised animal welfare and intense pain perception [7].…”
mentioning
confidence: 99%